Heavy Heparin: A Stable Isotope‐Enriched, Chemoenzymatically‐Synthesized, Poly‐Component Drug. Issue 18 (1st April 2019) - Cress, Brady F.; Bhaskar, Ujjwal; Vaidyanathan, Deepika; Williams, Asher; Cai, Chao; Liu, Xinyue; Fu, Li; M‐Chari, Vandhana; Zhang, Fuming; Mousa, Shaker A.; Dordick, Jonathan S.; Koffas, Mattheos A. G.; et al.
Abstract: Heparin is a highly sulfated, complex polysaccharide and widely used anticoagulant pharmaceutical. In this work, we chemoenzymatically synthesized perdeuteroheparin from biosynthetically enriched heparosan precursor obtained from microbial culture in deuterated medium. Chemical de‐ N ‐acetylation, chemical N ‐sulfation, enzymatic epimerization, and enzymatic sulfation with recombinant heparin biosynthetic enzymes afforded perdeuteroheparin comparable to pharmaceutical heparin. A series of applications for heavy heparin and its heavy biosynthetic intermediates are demonstrated, including generation of stable isotope labeled disaccharide standards, development of a non‐radioactive NMR assay for glucuronosyl‐C5‐epimerase, and background‐free quantification of in vivo half‐life following administration to rabbits. We anticipate that this approach can be extended to produce other isotope‐enriched glycosaminoglycans. Abstract : Pushing the envelope of deuterated drug development : Heavy heparin is chemo‐enzymatically synthesized from perdeuterated biosynthetic precursor, yielding the most complex stable isotope‐enriched pharmaceutical to date. Perdeuterated glycans will be valuable for pharmacological studies, contrast‐variation small angle neutron scattering, stimulated Raman scattering imaging, and as internal standards.